Treatment response of Epley’s manoeuvre in the management of posterior semicircular canal benign paroxysmal positional vertigo - Sharma, Rimjhim (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Benign paroxysmal positional vertigo (BPPV) is the most common reason for vertigo. Most common site of BPPV is posterior semicircular canal. The commonest symptom is episodic vertigo. This study aimed at the treatment response of Epley’s manoeuvre for posterior semicircular canal BPPV. Methods: 87 patients out of 114 were enrolled for the study from 2020 to 2021. After proper history and examination, Dix-Hallpike test (DHT) was done for diagnosis. Epley’s manoeuvre was done at first visit and was repeated at subsequent visits. Results: The mean age of the patients was 54 years. In this study, out of total 87 patients, there were 59 females (67.82%) and 28 males (32.18%). The male to female ratio was 1:2.11. Out of 87 patients, 53 patients (60.92%) recovered in the first visit, 18 patients (20.69%) recovered in second visit, 11 patients (12.64%) recovered in the third visit and remaining 5 patients (5.75%) recovered in fourth visit. In 3 out of 87 cases, that is, in 3.45%, recurrence was seen with return of the BPPV symptoms. Conclusions: Treatment response of Epley’s manoeuvre in posterior semicircular canal BPPV is good. Maximum number of patients’ recovered in the first visit.